Performance Contract System and Decentralised Education Service delivery in Kayonza District of Rwanda. - Mugabo Seth, Asiimwe (Kabale University, 2020)
This study examined the performance contract system and its influence on decentralized education service delivery. The study used a case study of Kayonza District. Data was obtained using interview as the major method of data collection and the use of a questionnaire. The study utilized a sample of 189 drawn from a population of 360 and adopted the statistical package for social science (SPSS) as the technique to quantitatively analyze the data obtained. The results obtained from the study indicated that performance contract influences decentralized education service delivery both positively and negatively by reducing absenteeism on the side of teachers and awakening the Government to timely supply resources in form of capitation grant to schools and rehabilitate classes to improve the environment for education service delivery. The effectiveness of the system in education service delivery was found out to be influenced by factors such as teachers’ awareness and adoption of the system, motivation, level of happiness and commitment involvement of implementers at all levels, working environment, availability of resources and teachers attitudes on the importance of performance contract while the challenges in the implementation of the system were found to include limited awareness, dishonesty, low motivation, poor learning environment poor perception and adoption, lack of ownership of the process and poor evaluation criterion. It was against this that various recommendations prescribed such as increasing teachers’ awareness, supplying the required resources, encouraging involvement of employees in target/goal setting, setting clear and appropriate evaluation criteria, strengthening continuous monitoring of system and adopting an all-inclusive reinforcement criterion to enhance effective implementation of the system in education sector.